A cohort study analyzing the impact of socioeconomic and spatial characteristics alongside treatment regimens on the environmental-health outcomes of the MDR-TB treatment in Pakistan - Arif, Ankasha; Ahmad, Eatzaz; Khan, Farzana Naheed; Fatima, Razia (Environmental science and pollution research international, 2021)
This study identifies and analyzes a number of factors that correlate with the environmental-health outcome of multi-drug resistance tuberculosis (MDR-TB) treatment in Pakistan. Survival analysis is carried out by applying the multivariable Cox Proportional Hazard model on secondary data of 369 patients registered at three main MDR-TB sites in Pakistan during 2012-2017. Results show that there is no difference in survival of patients between the two treatment arms, hospital and ambulatory care. Male gender and travel expenditure are found to be negatively associated with the environmental-health outcome, whereas spatial characteristic of time expenditure is positively related to it supporting distance bias approach. Medical expenditure is also positively related to the environmental-health outcome. The study concludes that availability of affordable and accessible health services, better environmental conditions, and ambulatory care based on WHO recommendation as well as health education along with social protection schemes should be ensured by the government to improve environmental-health outcome in the resource-scarce setting in Pakistan.